Keterkaitan Manajemen Peserta Didik Dengan Terlibatnya Siswa SMP Muhammadiyah 1 Medan Dalam Komunitas Geng Motor - Adinda Putri Sitepu; Anisa Putri; Dewi Wulandari; Enjelita Dwi Maharani; Elrisa Br Barus; Murni A. Situmorang (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Student management is a word that combines "management" and "students". Management is a strategy consisting of actions in the form of planning, organizing, mobilizing and controlling which are carried out to set and achieve predetermined goals using human resources and other resources. This research examines the relationship between student management and the involvement of Muhammadiyah 1 Medan Middle School students in the motorbike gang community. The type of research used is descriptive qualitative using a literature study approach. The results of the research explain the connection between student management and the involvement of Muhammadiyah 1 Medan Middle School students in the motorbike gang community because the regulations made by the school were negligent, the school did not provide outreach regarding the vision and mission of character education and the dangers of the motorbike gang community, as well as the lack of communication between student management with other management fields to provide direction or guidance regarding anticipatory handling of criminal acts that are rife among students.